Dyadic patterns of subjective cognitive reports as predictors of incident dementia. (20th December 2022) - Numbers, Katya T.; Lam, Ben C. P.; Crawford, John D.; Kochan, Nicole A.; Sachdev, Perminder S.; Brodaty, Henry
Abstract: Background: Subjective cognitive decline (SCD), in the absence of impaired clinical testing, may be a clinical indicator of early Alzheimer's disease (AD) and other dementias. However, not all individuals with SCD have cognitive decline. Corroboration of decline by an informant (i.e., close friend or family member) is one feature of SCD thought to increase the likelihood of preclinical AD. Few studies have examined whether different patterns of SCD in individuals and their informants are related to risk of dementia over time. Method: Data from 628 dyads comprising participants (M = 78.65 years, 56.1% female) and their informants from the Sydney Memory and Ageing Study were analysed to determine whether different dyadic patterns of SCD recorded at baseline were associated with differential risk of incident dementia ten years later. Four groups were formed by categorizing participants' and informants' responses on a binary SCD measure at baseline: [1] both participant and informant NO (n = 180, 28.7%); [2] participant YES, informant NO (n = 232; 36.9%); [3] participant NO, informant YES (n = 41; 6.5%); [4] Both YES (n = 175; 27.9%). We compared incident dementia risk across these groups and conducted Cox regression adjusting for demographics, APOE4 status, mood, and personality. Result: Figure 1 shows the incidence dementia risk of the four groups. After controlling for covariates in the Cox regression, compared to Group 1, participants in Group 3 were at higher risk of incident dementia over 10 years (HR = 2.35, p = .020) as were participants in Group 4 (HR = 2.24, p = .004). Participants in Group 4 were at greater risk of incident dementia than participants in Group 2 (HR = 1.61 p = .034; see Table 1). Conclusion: Participants from dyads where both individuals endorsed SCD at baseline, and where the informant, but not the participant endorsed SCD, had a more than two‐fold increased risk of progressing to dementia over 10 years. Our results, though preliminary, highlight the value of collecting both self‐ and informant SCD ratings in research and clinical contexts and suggest that informant reports of SCD may be especially important for identifying pre‐clinical AD.